2016
DOI: 10.1007/s00221-016-4559-y
|View full text |Cite
|
Sign up to set email alerts
|

Interference between adaptation to double steps and adaptation to rotated feedback in spite of differences in directional selectivity

Abstract: Two key features of sensorimotor adaptation are the directional selectivity of adaptive changes and the interference of adaptations to opposite directions. The present study investigated whether directional selectivity and interference of adaptation are related to executive functions and whether these phenomena differ between two methods for visuomotor adaptation. Subjects adapted at three target directions to clockwise or counterclockwise rotated feedback or to clockwise or counterclockwise target displacemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…However, Bastian points out that efficacy of stroke rehabilitation might be improved by methods that combine perceptual- and motor oriented approaches ( 6 ). A recent study with healthy participants showed a higher efficacy of a sensorimotor compared to a purely motor orientated approach, accordingly, although both approaches address the same adaptation mechanisms ( 7 ). An example for a perception-oriented approach for stroke rehabilitation is Ramachandran's mirror visual feedback method.…”
Section: Introductionmentioning
confidence: 99%
“…However, Bastian points out that efficacy of stroke rehabilitation might be improved by methods that combine perceptual- and motor oriented approaches ( 6 ). A recent study with healthy participants showed a higher efficacy of a sensorimotor compared to a purely motor orientated approach, accordingly, although both approaches address the same adaptation mechanisms ( 7 ). An example for a perception-oriented approach for stroke rehabilitation is Ramachandran's mirror visual feedback method.…”
Section: Introductionmentioning
confidence: 99%
“…Partial inhibition seems to be possible on the basis of cognitive executive inhibition. This is indicated by reports on facilitation of adaptation to two opposite directed sensorimotor discordances through explicit knowledge about these discordances (Imamizu, Sugimoto, Osu, Tsutsui, Sugiyama, Wada, et al, 2000) as well as by significant correlations between the amount of interference and participants' mental flexibility and cognitive inhibition abilities (Schmitz, 2016). Whereas these effects occur fast and are short-term, complete inhibition seldom occurs spontaneously.…”
Section: Connectivity Of Internal Models To Different Effectorsmentioning
confidence: 94%
“…Both parameters are significant covariates for the adaptation to increasing sensorimotor discordances [ 8 ]. Perseveration is also a predictor of the generalization of adaptation and the interference between consecutive adaptations [ 15 ]. Moreover, divergent thinking abilities predict how fast participants adapt [ 12 ].…”
Section: Methodsmentioning
confidence: 99%
“…Factor analyses indicate that the test performance primarily depends on action initiation (tasks 1 to 3), reading speed (task 1), nomination speed (task 2) and cognitive control of attention during interference (task 3) [ 33 , 34 ]. The performance in this test is a significant predictor of the interference between consecutive adaptations [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation